IMPLEMENTATION OF TOLERANCE-BASED LEARNING IN ISLAMIC RELIGIOUS EDUCATION - Khoiroh, Hadiatul; Iswandi, Iswandi; Azis, Lasman; Alwizra (Mandeh : Jurnal Pendidikan Islam, 2024)
This study aims to describe the implementation of tolerance-based learning in Islamic Religious Education and analyze its impact on students' religious attitudes and character. The background of this research stems from the need for education that emphasizes not only cognitive aspects but also fosters an awareness of living in harmony within diversity. Islamic Religious Education plays a strategic role in instilling values ​​of tolerance so that students are able to practice Islamic teachings wisely, moderately, and civilized. The research method used was qualitative research, with data collection techniques through observation, interviews, and documentation. The study subjects included Islamic Religious Education teachers and secondary school students. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of tolerance-based learning is carried out by integrating the values ​​of mutual respect, respect for differences, and fostering an attitude of moderation in every learning activity. Islamic Religious Education teachers use a dialogical approach, case studies, group discussions, and value reflections to encourage students to understand religious teachings in an inclusive manner. The impact of this implementation is an increase in mutual respect, cooperation, and social awareness among students, while reducing the potential for exclusive or intolerant attitudes. The conclusion of this study is that tolerance-based learning in Islamic Religious Education can be an effective strategy for developing students who are faithful, have noble morals, and are able to live harmoniously in diversity. The implementation of this strategy is also relevant to national education goals and the values ​​of religious moderation emphasized in the Independent Curriculum.